Fungal endophyte assemblages associated with twigs of olives in the Core Cape Subregion, South Africa - Ngubane, Nombuso Portia (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDConsEcol)--Stellenbosch University, 2022.